Provisão do Programa “Minha Casa Minha Vida” em São José do Rio Preto – SP : inserção, adequação urbana e socioeconômica de empreendimentos habitacionais - Meireles, Eduardo (2016)
The development of a nation is directly linked to the solution of their major social problems. In Brazil, the housing deficit stands out among the social problems that need solving. However, the Brazilian government has spent the last 30 years without directing a massive investment in housing, sanitation and transport, which in turn caused serious problems in Brazilian cities. Since 2005, considering the emergence of solutions to this issue, it is observed by the federal government the resumption of investments, which gave priority to some concentrated management tools, based on the central axis of infrastructure producing that supports economic activities. At the end of the 2000s, with the worsening of an economic crisis of global reach, the federal government adopts a Keynesian and anti-cyclical strategy to resume growth: investment in public policies in housing area with the housing program called "Minha Casa, Minha Vida" (MCMV). From the urban point of view, the measures taken by the government originated sociospatial segregation and environmental problems, since the state does not equated the access to housing with city distribution, because it markedly prioritized the economic area of the PMCMV, insofar as the focus returned to the mass production of dwelling units. This work aims to understand the provision of the PMCMV in the city of São José do Rio Preto, São Paulo, Brazil, by analyzing the urban integration and socio-economic and urban appropriateness of two projects from the category 2 in the city in question. The methodology for this work was a quantitative research following the survey method (Babbie, 1999), besides using the qualitative research strategies, such as the study of post-facto case (Yin, 2010). For the application of quantitative research, 302 residents of two projects were interviewed according to a sample calculation. Then it was used a descriptive approach to treating the location of enterprises and public facilities. Based on the results of survey research, there was a correlation analysis and a factor and cluster analysis to check the interaction between the studied variables. Some researches and analysis show that PMCMV ventures in the city of São José do Rio Preto, São Paulo from the category 2 have problems of urban integration, peripheral location with limited access to transportation, health and education, as well as other issues to be addressed in this study. In conclusion, it was found a series of actions are still needed in order to perpetuate, deepen and broaden the access to housing from the point of view of public policies. Our reflections lead us to realize that the right to decent and adequate housing goes beyond distributing houses on the peripheries of cities, because it includes actions such as land-location distribution, urbanized land, a better oversight in the country of the regulation concerning the use and occupation of urban land.